Zdazyc przed Panem Bogiem - Krall, Hanna (Krakow : Wyd. Literackie, 1989)
A narrative about the deportation of Jews from Poland, and the manner in which they were saved.
Keywords: World War, 1939-1945 -- Jews -- Rescue; World War, 1939-1945 -- Deportations from Poland; Jews -- Poland